QS ranks Universiti Malaysia Pahang among world’s best - Irene, Wei Kiong Ting (2019)
Universiti Malaysia Pahang (UMP) (www.ump.edu.my) has once again made Malaysia proud, achieving another milestone in QS university rankings along its path toward being a distinguished technological university. This time around, QS World University Rankings (WUR) 2020 it is for UMP; securing a spot for the first time, UMP has further established its standing as one of the world-class universities in the world map (top 1.8% of universities in Asia, top 2.6% in the world, five-stars rated).